Child Protection, Child Deaths, Politics and Policy Making: Numbers as Rhetoric - Harrison, Celine; Harries, Maria; Liddiard, Mark (Cambridge University Press, 2018)
Child welfare policy making is a highly contested area in public policy. Child abuse scandals prompt critical appraisals of parents, professionals and the child protection system creating a tipping point for reform. One hundred and six transcripts of debates in the West Australian Parliament from August until December 2006 relating to child welfare and child deaths were analysed using qualitative content analysis. The analysis found that statistics about child deaths were conflated with other levels of childhood vulnerability promoting blame, fear, risk and an individual responsibility theme. The key rhetorical strategy was the use of numbers to generate emotion, credibility and authority to frame child maltreatment narrowly as a moral crime. Rhetoric and emotions is about telling causal stories and will remain ubiquitous in social policy making. So, in order to guide policy debate and creation, ground their claims and manage ambiguity and uncertainty, policy makers, researchers and practitioners working with complex social issues will do well to step into this public and political discourse and be strategic in shaping more nuanced alternative frames.